The Social Hierarchy of Arab and Non-Arab Peoples in Classical Islamic History: A Historical and Sociological Analysis - Muhamad Yusrul Hana; Affan Ismail; Ismail Hamid (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
Islam, brought by the Prophet Muhammad, upholds the principle of human equality, but in classical Islamic history, there were dynamics and tensions between normative ideals and social reality. This study aims to examine the social stratification of Arab and non-Arab due to cultural, political, and power policy factors from the time of the Prophet Muhammad to the Abbasid Dynasty. This study uses a historical and sociological approach, focusing on the concepts of social stratification and social status. The methods used are historical research methods, including heuristics, criticism, interpretation, and historiography. The results of this study are, first, that classical Islamic society formed its social hierarchy based on status and stratification, consisting of Arabs, mawali, dhimmi, and enslaved people. Second, the social order in classical Islamic society, shaped by social stratification, was influenced by political, religious, and cultural policies guided by two key elements: the royal elite as the highest authority and the religious elite as the theological authority.